The effect of skipping combination with body weight training on cardiorespiratory endurance and body mass index (BMI) as a covid-19 prevention effort for overweight adolescents - Nasrulloh, Ahmad; Yuniana, Rina; Pratama, Kukuh Wahyudin (Jurnal Keolahragaan, 2021)
This study aims to determine the effect of skipping combination with body weight training on cardiorespiratory endurance and BMI as an effort to prevent Covid 19 for overweight adolescents. This research is an experimental research. In this study, treatment was given in the form of skipping exercise combined with body weight training for 8 weeks with a frequency of 3 times / week, an intensity of 60%-70% MHR with a duration of 30 minutes. The population in this study were teenagers. Sampling was done by purposive sampling on adolescents aged between 17-21 years and overweight. Instrument used to measure VO2 max with MFT (multistage fitness test) and measurement of height and weight to determine BMI. The data analysis technique used prerequisite test and paired t test. Based on the results of the cardiorespiratory endurance data analysis, the t-count value was 10.495 with a significance value of 0.000, it can be concluded that there is a significant effect of skipping combination with body weight training on cardiorespiratory endurance in overweight adolescents. The mean value of the cardiorespiratory endurance pretest was 34.92 and the posttest average increased to 40.05. While the results of the analysis on BMI data obtained a t-count value of 15.293 with a significance value of 0.000, it can be concluded that there is a significant effect of skipping combination with body weight training on BMI in overweight adolescents. The mean value of the BMI pretest was 26.60 and the posttest average BMI decreased to 22.19. So it can be concluded that skipping exercises combined with body weight training can increase cardiorespiratory endurance and reduce BMI as an effort to prevent Covid 19 for overweight adolescents.